2009
DOI: 10.2172/984946
|View full text |Cite
|
Sign up to set email alerts
|

Radar cross section of triangular trihedral reflector with extended bottom plate.

Abstract: Trihedral corner reflectors are the preferred canonical target for SAR performance evaluation for many radar development programs. The conventional trihedrals have problems with substantially reduced Radar Cross Section (RCS) at low grazing angles, unless they are tilted forward, but in which case other problems arise. Consequently there is a need for better low grazing angle performance for trihedrals. This is facilitated by extending the bottom plate. A relevant analysis of RCS for an infinite ground plate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…Our reference targets are two triangular trihedral reflectors (also known as corner reflectors) composed of three orthogonal triangular conducting plates. Trihedral targets have a large RCS for their size and a low angular variability in RCS around their boresight (Atlas, 2002;Brock and Doerry, 2009;Chandrasekar et al, 2015). One reflector has a size parameter of 10 cm, with a maximum theoretical RCS at our radar operation frequency of 16.30 dBsm.…”
Section: Equations Used In Radar Calibrationmentioning
confidence: 99%
“…Our reference targets are two triangular trihedral reflectors (also known as corner reflectors) composed of three orthogonal triangular conducting plates. Trihedral targets have a large RCS for their size and a low angular variability in RCS around their boresight (Atlas, 2002;Brock and Doerry, 2009;Chandrasekar et al, 2015). One reflector has a size parameter of 10 cm, with a maximum theoretical RCS at our radar operation frequency of 16.30 dBsm.…”
Section: Equations Used In Radar Calibrationmentioning
confidence: 99%
“…Furthermore, an azimuth deviation of less than 0.5° and elevation deviation of less than 0.5° could introduce no more than 0.5-dB RCS loss at the X-band. However, a pointing deviation of less than 0.5° in azimuth and elevation could make the resulting RCS within about 0.1 dB of the peak value for monostatic calibration [25]. By comparing the two results, we found that the RCS loss due to pointing deviation was more severe for bistatic calibration.…”
Section: Pointing Deviationmentioning
confidence: 84%
“…Consider a TCR with sides comprised of isosceles right triangles. With the geometry defined as per Figure 4, by using geometrical optics approximation theory, the RCS of a TCR can be formulated as [25]:…”
Section: Monostatic Bistatic Equivalence Theoremmentioning
confidence: 99%
“…In principle, the reflector should be characterized by a reflectivity much higher than that of the surrounding scatterers [7]; that is to say, the reflector should have a high RCS for a relative small size. Some of the most common corner reflectors being used are flat plate, dihedral, triangular trihedral, and cubic trihedral, and their featured RCSs [11] are listed in Table 1. From the table, we can see that the circular trihedral offers the greatest RCS.…”
Section: The Shape Of Corner Reflectormentioning
confidence: 99%